Improving productivity and efficiency of assembly line in a Small Medium Industry (SMI) manufacturing company using witness simulation / M.S.M. Sani, M.F.F.A. Rashid and T.N.B.B. Khan - Sani, M.S.M.; Rashid, M.F.F.A.; Khan, T.N.B.B. (2008)
In this competitive world, manufacturing company is one of the sectors which is competing to gain demand and satisfactory from customers. Dealing with continuous competition, companies not only need to produce quality products, but excellent production system and management also play an important role. The aim of this paper is to improve the productivity and efficiency of a manual assembly line in a Small Medium lndustry (SMI). Various industrial engineering techniques and tools are implemented in this study in order to investigate and solve the problem that occurs in the production line. This assembly line is studied using time study techniques, and analyzed and solved using line balancing and simulation approach. The time study techniques applied are using stopwatch time study and identifying operation process procedures. Simulation provides the best solution for comparing, predicting and optimizing the performance of a system without affecting the existing system or cost of implementing a new actual process. This project presents the application of Witness as a simulation tool for manipulation of the data. Initially, the current layout of existing assembly line did not achieve the targeted output. Therefore, three new layouts are discussed and one layout which has the highest improvement in terms of productivity and efficiency is chosen. Simulation definitely plays a vital role in design and operation of nowadays' manufacturing production line system.